2000
DOI: 10.1073/pnas.97.12.6544
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of stem/progenitor cells by sulfated polysaccharides does not require selectin presence

Abstract: Employing carbohydrate ligands, which have been extensively used to block selectin function in vitro and in vivo, we have examined the involvement of such ligands in stem͞progenitor cell mobilization in mice and monkeys. We found that sulfated fucans, branched and linear, are capable of increasing mature white cells in the periphery and mobilizing stem͞progenitor cells of all classes (up to 32-fold) within a few hours posttreatment in a dosedependent manner. To elicit the effect, the presence of sulfate groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 36 publications
(31 reference statements)
4
69
0
Order By: Relevance
“…21 While evaluating the role of selectins in the mobilization process, we and others found that fucoidan, a sulfated fucose polymer known to interact with P-and L-selectins and to inhibit leukocyte rolling and inflammatory responses in vivo, [22][23][24] can rapidly mobilize progenitors into the peripheral blood compartment. 25,26 This effect was accentuated in endothelial selectindeficient mice, indicating that the presence of selectins was not required for fucoidan-induced mobilization. Further studies have suggested that fucoidan increased the levels of stromal cell-derived factor (SDF-1 or CXCL12) in the blood, an effect that may contribute to its mobilizing activity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…21 While evaluating the role of selectins in the mobilization process, we and others found that fucoidan, a sulfated fucose polymer known to interact with P-and L-selectins and to inhibit leukocyte rolling and inflammatory responses in vivo, [22][23][24] can rapidly mobilize progenitors into the peripheral blood compartment. 25,26 This effect was accentuated in endothelial selectindeficient mice, indicating that the presence of selectins was not required for fucoidan-induced mobilization. Further studies have suggested that fucoidan increased the levels of stromal cell-derived factor (SDF-1 or CXCL12) in the blood, an effect that may contribute to its mobilizing activity.…”
Section: Introductionmentioning
confidence: 91%
“…Since fucoidan can mobilize progenitors from the BM to the blood compartment in a selectin-independent manner 25,26 and recent experimental evidence has linked mobilization with myeloid cells, 2,5,6,29 we hypothesized that fucoidan might interact with other receptors on the surface of myeloid cells. To investigate this possibility, BMNCs were stained with biotinylated fucoidan (BFuc) and bound fucoidan detected by flow cytometry.…”
Section: Fucoidan Binds To Nonselectin Receptors On Myeloid Cellsmentioning
confidence: 99%
“…28,61 Mobilization could also be achieved by the administration of some types of polysaccharides (for example, zymosan or fucoidans) that in animal models have been demonstrated to efficiently mobilize HSPCs within 1 h after a single injection. 66,67 Elements of innate immunity involved in stem cell mobilization Evidence from our, [41][42][43][44]68 and other laboratories 69,70 indicates that innate immunity orchestrates egress of HSPCs from BM into PB. Innate or natural immunity is inborn and thus naturally present in an organism; it does not require previous sensitization to an antigen.…”
Section: Pharmacological Mobilization Of Hspcsmentioning
confidence: 99%
“…Different groups found that the selectin inhibitor fucoidan increased circulating hematopoietic progenitors (HSPCs) independently of selectin function. 6,7 The hypothesis was advanced that sulfated glycans expressed in the BM microenvironment, like sulfatide, might regulate HSC trafficking. Sulfatide, a major component of myelin, is synthetized by the UDPgalactose:ceramide galactosyltransferase (Cgt) enzyme.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%